Screening and management of hypertensive patients with chronic kidney disease referred to Hypertension Excellence Centres among 27 countries. A pilot survey based on questionnaire - Halimi, Jean Michel; Sarafidis, Pantelis; Azizi, Michel; Bilo, Grzegorz; Burkard, Thilo; Bursztyn, Michael; Camafort, Miguel; Chapman, Neil; Cottone, Santina; de Backer, Tine; Deinum, Jaap; Delmotte, Philippe; et al. (Journal of Hypertension, 2024)
Objective: Real-life management of hypertensive patients with chronic kidney disease (CKD) is unclear. Methods: A survey was conducted in 2023 by the European Society of Hypertension (ESH) to assess management of CKD patients referred to ESH-Hypertension Excellence Centres (ESH-ECs) at first referral visit. The questionnaire contained 64 questions with which ESH-ECs representatives were asked to estimate preexisting CKD management quality. Results: Overall, 88 ESH-ECs from 27 countries participated (fully completed surveys: 66/88 [75.0%]). ESH-ECs reported that 28% (median, interquartile range: 15–50%) had preexisting CKD, with 10% of them (5–30%) previously referred to a nephrologist, while 30% (15–40%) had resistant hypertension. The reported rate of previous recent (<6months) estimated glomerular filtration rate (eGFR) and urine albumin–creatinine ratio (UACR) testing were 80% (50–95%) and 30% (15–50%), respectively. The reported use of renin-angiotensin system blockers was 80% (70–90%). When a nephrologist was part of the ESH-EC teams the reported rates SGLT2 inhibitors (27.5% [20 – 40%] vs. 15% [10 – 25], P ¼ 0.003), GLP1-RA (10% [10 – 20%] vs. 5% [5 – 10%], P ¼ 0.003) and mineralocorticoid receptor antagonists (20% [10 – 30%] vs. 15% [10 – 20%], P ¼ 0.05) use were greater as compared to ESH-ECs without nephrologist participation. The rate of reported resistant hypertension, recent eGFR and UACR results and management of CKD patients prior to referral varied widely across countries. Conclusions: Our estimation indicates deficits regarding CKD screening, use of nephroprotective drugs and referral to nephrologists before referral to ESH-ECs but results varied widely across countries. This information can be used to build specific programs to improve care in hypertensives with CKD.
CRIS-Team Scopus Importer:2024-08-16
Keywords: albuminuria; chronic kidney disease; glomerular filtration rate; hypertension; management; screening